PERBANDINGAN HUKUM INDONESIA DAN INDIA TERHADAP PENYELESAIAN SENGKETA ARBITRASE SECARA ONLINE - Fathurrahman, Muhammad Angga; Husna, Lenny (Universitas Ekasakti, 2023)
This article aims to find out the comparison of Indonesian and Indian law to the existence of online arbitration. Comparison of laws by comparing the national legal arrangements of each country. This research uses normative legal research which is prescriptive in nature. The approach used in this research is the statute approach and the comparative approach. The legal materials used in the research are primary and secondary legal materials with data collection techniques using library research. The method of legal analysis is carried out in a syllogistic manner by conducting an analysis in general and then withdrawing it specifically. Based on the research and discussion, it can be concluded that arbitration is an alternative method of dispute resolution, economic development and globalization are expanding the reach of the community to form business agreements both nationally and internationally. The legal systems of Indonesia and India have not specifically regulated online arbitration. The national laws of these two countries generally regulate the application of online arbitration, but the application of online arbitration can be carried out if the procedure does not violate the provisions of national law. The arbitral institutions of the two countries, namely the Indonesian National Arbitration Board (BANI) and the Indian Council of Arbitration (ICA) have regulated procedural rules that each apply in the two countries.